2021
DOI: 10.3390/vetsci8020028
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine and Tear Production: Evaluation in Dogs as Spontaneous Model for Ocular Surface Disorders

Abstract: Tear film provides lubrication and protection to the ocular surface. The sedation reduces tear production, often leading to perioperative exposure keratopathy. The aim of the present study was to report the effects of intramuscular dexmedetomidine on canine tear production, measured by STT-1, for an experimental period of 8 h after sedation. Ten dogs who underwent sedation for routine radiologic assessment were recruited for the study. In all animals, tear production in right and left eyes was measured 15 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…This study continues previous research on the effect of sedative and anesthetic drugs on tear production in domestic animals, of which a note on the canine tear reduction by dexmedetomidine has already been published [5]. During the experimental period, no dogs exhibited corneal damages.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This study continues previous research on the effect of sedative and anesthetic drugs on tear production in domestic animals, of which a note on the canine tear reduction by dexmedetomidine has already been published [5]. During the experimental period, no dogs exhibited corneal damages.…”
Section: Discussionsupporting
confidence: 83%
“…Tear production was measured according to our own methodology previously reported [ 5 ]. The STT 1 Tear Test (Tear Strips, Biovision Limited, Dunstable, UK) was performed in both eyes, recording baseline values expressed in millimeters/minute.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Kilic and Sarierler [ 31 ] reported that tear production was significantly depressed after the dogs were sedated with propionyl promazine-fentanyl, diazepam-fentanyl, propofol, and thiopental. In addition, Dartt [ 32 ] found that the combinations of diazepam with butorphanol, acepromazine with oxymorphone, and xylazine with butorphanol decreased tear production, which may induce corneal ulcers in dogs after prolonged anesthesia [ 33 ], and moisturizing lubricant eye drops have been recommended during anesthesia to prevent corneal discomfort [ 34 ]. However, the evaluation of decreasing tear production was beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%